The Development Mobile Application With App Inventor For Young Learners In Establishing Anti-Corruption Behavior - Wicaksono, Zaenurokhman Pipit; Waluyo, Edi (Jurusan PGPAUD FIP UNNES, 2018)
There are so much effect caused by globalization, one thing that is affected is the world of education. The world of education requires people to think more creative and innovative. That’s made humans to be more advanced in live their life in this modern era. But, the development of technology doesn’t just have a positive impact; it also has a negative impact. One of it is the corruption behavior, which is an extraordinary crime that hurt many people. This research aims to develop modern media learning that is mobile application which have a theme ‘anti-corruption for young learners’. This research is a Reach and Development Research that begin with problem analysis, needs analysis, product design, design validation, and the final product trial. This research used quantitative descriptive analysis.  The result of validation show that media is feasible to used as media learning , according to media specialist appraisal 81.5% and 80.3% according to material specialist.The result of effectiveness of mobile application show that the distribution t, if dk=9 obtained from dk n-1= 10-1=9, with an error 5%, then the price of t-table 2,262. If the price of t same with Ha, then Ha can be accepted. Based on calculation, t = 23,917 which falls on the acceptance of Ha which means rejection by Ho. Then it can be concluded that there is a significant differences between the effectiveness of learning using mobile application and the conventional method. Besides that, learning with mobile application can improve the behavior of anti corruption, honesty, responsibility, courage, l